Effect of chromium–titanium on corrosion and erosion of HVOF coating. (3rd April 2022) - Sharma, Ratnesh Kumar; Das, Randip Kumar; Kumar, Shiv Ranjan
ABSTRACT: The high-velocity oxyfuel spraying (HVOF) method was used to coat Fe–Cr–Ti-based coating material Fe60Mo5C15Si10Cr0Ti10, Fe50Mo5C15Si10Cr10Ti10, Fe50Mo5C15Si10Cr10Ti0 on base material 316L stainless steel. A comparative analysis was performed to investigate the effect of alloying element chromium and titanium on corrosion and erosion properties of Fe–Cr–Ti coating material. NaCl solution (3.5 wt.) was used for the study of corrosion behaviour. The steady-state erosion wear was examined by varying parameters such as impact speed and impact angle. It was found that the micro-hardness and fracture toughness of Fe–Cr–Ti coating material with 10 wt-% titanium were 18.02 and 5.08% more than those of the coating material with 10 wt-% chromium, respectively. This showed that titanium played a more significant role than chromium in terms of mechanical and erosion properties and a less significant role in terms of corrosion behaviour. Fe50Mo5C15Si10Cr10Ti10 indicated the least wear and a smooth surface with very few pores and wear scars.